2018
DOI: 10.4236/fns.2018.97061
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Characteristics of Arabinoxylan Gels?

Abstract: Arabinoxylan gels are commonly characterized to determine the feasibility of utilizing them in numerous applications such as drug delivery systems. The general characteristics of numerous types of arabinoxylan gels as well as their susceptibility to degradation are discussed in this manuscript. There are two main types of arabinoxylan: water-extractable and alkali-extractable. The physicochemical characteristics of the arabinoxylan determine its extractability and gelling characteristics. Gels can be created f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Figure 6c shows the strain spectrum of AX gels, with elastic behavior dominating over the viscous one (G' > G'') and tan δ (G''/G') values below 1, indicating a gel-like consistency in the strain range investigated. Both frequency and strain spectra are similar to the results reported in previous studies [25,32,44,45]. These data confirm that below the rheological conditions used in the present study, AX gel is stable, the structure is not easily disturbed.…”
Section: Size Distribution Of Naxsupporting
confidence: 92%
“…Figure 6c shows the strain spectrum of AX gels, with elastic behavior dominating over the viscous one (G' > G'') and tan δ (G''/G') values below 1, indicating a gel-like consistency in the strain range investigated. Both frequency and strain spectra are similar to the results reported in previous studies [25,32,44,45]. These data confirm that below the rheological conditions used in the present study, AX gel is stable, the structure is not easily disturbed.…”
Section: Size Distribution Of Naxsupporting
confidence: 92%
“…S1 C) was influenced negatively by AX addition in all dough system except native normal wheat dough, where no difference was found between the value of base dough and AX added doughs. The observed dough weakening effect of AX addition was in accordance with other findings [47]. The same stability lowering effect was found in case of AX incorporation as in AX addition.…”
Section: Comparative Analysis Of Ax Addition and Ax Incorporationsupporting
confidence: 92%
“…In case of the other two wheat types, the tendency of consistency growth was similar, but its extent was slightly lower than that of normal wheat. The higher consistency of AX dosed doughs at constant water absorption can be explained by the fact that AXs act as hydrocolloids binding significant amount of water [47].…”
Section: Comparative Analysis Of Ax Addition and Ax Incorporationmentioning
confidence: 99%
“…Laccase-produced radicals were probably responsible for this phenomenon. Radicals participating in secondary reactions may have led to a beginning degradation of the AX main chains [46]. It was recently reported that a 90 min heat treatment at 85 • C significantly decreased the laccase activity.…”
Section: Storage Stability Of Arabinoxylan Gelsmentioning
confidence: 99%
“…Cross-linking of AX with LccFtr and LccPpu formed elastic gels with viscoelastic properties comparable to gelatin gels. AX gels, like traditional gelatin gels, do not raise nutritional concerns as Bifidobacterium enzymes present in the human large intestine degrade them [46]. The covalent structure of cross-linked AX gels confers them some superior characteristics, such as high water absorption capacity and stability to pH, temperature, and ionic charges [32].…”
Section: Viscoelastic Properties Of Ax and Gelatin Gelsmentioning
confidence: 99%